Improved Coordinated Control of Coal-fired Power Units with Large-scale Renewable Energy Integration by Introducing Battery Energy Storage System. Issue 1 (March 2021) - Zhang, Guangming; Niu, Yuguang; Wang, Wei; Gan, Zhiyong; Tang, Ningning
Abstract: With a high proportion of renewable energy being connected to the grid, the stable operation of the power system has been severely challenged. Conventional coal-fired power units need to take measures to compensate for random fluctuations in renewable power generation. This study introduces the battery energy storage system (BESS) to the coordinated control system (CCS) of the coal-fired units to improve the load regulation. Firstly, the dynamic models of boiler-turbine unit and BESS are set up. Furthermore, an improved coordinated control system combined with boiler, turbine, and BESS is designed. A dual controller that consists of BESS and fuel control is proposed to improve the power ramp rate. Finally, a power step simulation in a 330 MW coal-fired power unit is conducted. The simulation results show that the power ramp rate is 60 MW/min and the AGC performance index reaches 7.68 with the improved strategy.